Insulin U-500 in severe insulin resistance in type 2 diabetes mellitus. Issue 1002 (5th May 2009) - Crasto, W; Jarvis, J; Hackett, E; Nayyar, V; McNally, P G; Davies, M J; Lawrence, I G
Abstract : Some patients with type 2 diabetes mellitus (T2DM) are profoundly insulin resistant and require large insulin doses to achieve optimal glycaemic control. However, large volumes of subcutaneous conventional U-100 insulin can cause discomfort at the injection site, resulting in poor concordance with insulin therapy. One therapeutic option is the use of U-500 insulin, thus reducing the insulin volume by 80%. This review will address the practical issues associated with the use of U-500, clinical efficacy and safety aspects of this concentrated insulin, which has an important role in a subgroup of patients with T2DM.